2017
DOI: 10.1007/s40265-017-0789-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Negative Symptoms in Schizophrenia: A Comprehensive Review

Abstract: Negative symptoms (such as amotivation and diminished expression) associated with schizophrenia are a major health concern. Adequate treatment would mean important progress with respect to quality of life and participation in society. Distinguishing primary from secondary negative symptoms may inform treatment options. Primary negative symptoms are part of schizophrenia. Well-known sources of secondary negative symptoms are psychotic symptoms, disorganisation, anxiety, depression, chronic abuse of illicit drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 188 publications
2
59
0
1
Order By: Relevance
“…Traditional pharmacotherapy, based on the dopamine theory of schizophrenia, has several significant limitations. The use of antipsychotics improves predominantly positive symptoms, although there is evidence of improvement of negative symptoms with the use of clozapine (Kane, 1988) and aripiprazole (Veerman et al, 2017). Approximately 25% of patients are resistant to therapy (Remington et al, 2017), in addition, the rate of metabolic syndrome among patients was 32.5% (Mitchell et al, 2013), which worsens life quality and predisposes to cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional pharmacotherapy, based on the dopamine theory of schizophrenia, has several significant limitations. The use of antipsychotics improves predominantly positive symptoms, although there is evidence of improvement of negative symptoms with the use of clozapine (Kane, 1988) and aripiprazole (Veerman et al, 2017). Approximately 25% of patients are resistant to therapy (Remington et al, 2017), in addition, the rate of metabolic syndrome among patients was 32.5% (Mitchell et al, 2013), which worsens life quality and predisposes to cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were mainly conducted in patients with general symptoms of schizophrenia, therefore a secondary effect on negative symptoms could not be ruled out. Therefore negative symptom improvement cannot be considered a core component of atypicality (Veerman et al, 2017). Previous studies have demonstrated that no drug had a beneficial effect on negative symptoms when compared to another drug (Arango et al, 2013;Millan et al, 2014;Fusar-Poli et al, 2015), meaning that head to head comparisons of different agents among each other did not result in superiority of one drug to another.…”
mentioning
confidence: 99%
“…Topiramate, a new antiepileptic drug, which is increasingly being used as a mood stabilizer in bipolar disorder, and does not cause parkinsonism, has also been used as adjuvant therapy for both the positive and negative symptoms of schizophrenia. [15][16][17] And it holds some promise as an adjunctive therapy for both overweight and treatment of psychotic symptoms. 5 Topiramate has the strongest mean weight loss compared with placebo, metformin, H2 receptor antagonists, and norepinephrine reuptake inhibitors in some reviews 5,8,18,19 although it has some adverse events which are possibly uncommon.…”
Section: Introductionmentioning
confidence: 99%